Minimization of water consumption in fresh-cut salad washing by UV-C light. (April 2015) - Ignat, Alexandra; Manzocco, Lara; Bartolomeoli, Ingrid; Maifreni, Michela; Nicoli, Maria Cristina
Abstract: The decontamination effect of UV-C light at increasing fluence up to 1.2 kJ/m 2 was studied with reference to natural microflora and inoculated pathogens in lamb's lettuce wash water. UV-C light dose of 0.4 kJ/m 2 allowed to inactivate most of the native microflora and to achieve more than 5- Log-reductions in inoculated microorganisms ( Salmonella enterica, Listeria monocytogenes and Escherichia coli ). In multiple washing cycles up to 5, UV-C light treatment allowed to obtain more than 3-log reductions in native microflora in wash water. Spectral properties indicated that, independently on the number of recycling cycles, a considerable amount of UV-C light can penetrate wash water if its thickness is lower than circa 1 cm. Highlights: UV-C light allows decontamination of wastewater from salad washing. UV-C light at 0.4 kJ/m 2 promoted 5-Log reductions in inoculated pathogens. Wastewater spectral properties do not impair UV-C light decontamination efficacy. Decontaminated wastewater can be recycled for up to 5 washing cycles.